Delayed onset serotonin syndrome in the setting of polypharmacy - Roshan Acharya; Smita Kafle; Sijan Basnet; DilliRam Poudel; Sushil Ghimire (Journal of Community Hospital Internal Medicine Perspectives, 2021)
Serotonin syndrome is a rare but well-known condition that can be life-threatening if not diagnosed early. Onset is usually within 4 to 13 h of starting the offending medication. We present a case of delayed onset of serotonin syndrome that presented after 48 h. Polypharmacy played a role in causing the onset of symptoms. Clinicians should keep a high index of suspicion for serotonin syndrome when dealing with elderly confused patients who take multiple medications even when the onset is delayed or atypical because the outcome can be disastrous.